Recent advances in impact analysis methods for ex-post impact assessments of agricultural technology: options for the CGIAR - Janvry, A. de; Dustan, A.; Sadoulet, E. (CGIAR Independent Science and Partnership Council, 2011)
This paper was commissioned by SPIA in 2010 and appraises a range of recent methodological innovations that are now available to practitioners when carrying out analysis of the impact of agricultural research. It argues for greater focus on methods that provide rigorous casual reference.